Synonymous Mutations in the Phosphoglycerate Kinase 1 Gene Induce an Altered Response to Protein Misfolding in Schizosaccharomyces Pombe - Levican-Jaque, G (Frontiers Media S.A., 2023)
Background: Proteostasis refers to the processes that regulate the biogenesis, folding, trafficking, and degradation of proteins. Any alteration in these processes can lead to cell malfunction. Protein synthesis, a key proteostatic process, is highly-regulated at multiple levels to ensure adequate adaptation to environmental and physiological challenges such as different stressors, proteotoxic conditions and aging, among other factors. Because alterations in protein translation can lead to protein misfolding, examining how protein translation is regulated may also help to elucidate in part how proteostasis is controlled. Codon usage bias has been implicated in the fine-tuning of translation rate, as more-frequent codons might be read faster than their less-frequent counterparts. Thus, alterations in codon usage due to synonymous mutations may alter translation kinetics and thereby affect the folding of the nascent polypeptide, without altering its primary structure. To date, it has been difficult to predict the effect of synonymous mutations on protein folding and cellular fitness due to a scarcity of relevant data. Thus, the purpose of this work was to assess the effect of synonymous mutations in discrete regions of the gene that encodes the highly-expressed enzyme 3-phosphoglycerate kinase 1 (pgk1) in the fission yeast Schizosaccharomyces pombe. Results: By means of systematic replacement of synonymous codons along pgk1, we found slightly-altered protein folding and activity in a region-specific manner. However, alterations in protein aggregation, heat stress as well as changes in proteasome activity occurred independently of the mutated region. Concomitantly, reduced mRNA levels of the chaperones Hsp9 and Hsp16 were observed. Conclusion: Taken together, these data suggest that codon usage bias of the gene encoding this highly-expressed protein is an important regulator of protein function and proteostasis. Copyright © 2023 Moreira-Ramos, Arias, Flores, Katz, Levicán and Orellana.